HUBUNGAN TINGKAT PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN KETERAMPILAN MENYIKAT GIGI PADA SISWA KELAS IV SDN 5 DAUH PURI DI WILAYAH KERJA PUSKESMAS II DENPASAR BARAT TAHUN 2023 - Ni Made Sirat; Ni Nyoman Dewi Supariani; Asep Arifin Senjaya; Ni Luh Ria Aprililia (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
The (2018)Â Basic Health Research stated that the population of the province of Bali had dental and oral health problems by 41.06%, for the 5-9 year age group it was 51.7% and for the 10-14 year age group it was 34.4%. Denpasar City has dental and oral health problems of 40.66%, this data shows that people in Denpasar City have quite a high number of dental and oral health problems, this is related to people's habits in brushing their teeth. The purpose of this study was to describe the level of knowledge regarding dental and oral health care and teeth brushing skills in class IV students at SDN 5 Dauh Puri, West Denpasar, in 2023. This type of research was descriptive research using a total population of 32 respondents. Research resultÂ the percentage of knowledge with good criteria (12.5%), sufficient criteria (40.6%), poor criteria (46.9%). The average knowledge is 57.34 with sufficient criteria. The percentage of skills with very good criteria (6.2), good criteria (25%), sufficient criteria (46.9%), needing guidance criteria (21.9%). Average skill 62.5 criteria sufficient. The conclusion is that the average level of knowledge about dental and oral health maintenance of students is in the sufficient criteria and the average teeth brushing skills are in the sufficient criteria. Skills based on the level of knowledge show students have sufficient criterion skills with sufficient criterion knowledge levels.